ANALISIS HUBUNGAN TUTUPAN LAHAN DAN INDIKATOR KESEHATAN HIDROLOGI DAS REJOSO, JAWA TIMUR - Wariunsora, Sisilia; Kusuma, Zaenal; Suprayogo, Didik (Jurnal Tanah dan Sumberdaya Lahan, 2024)
With increasing concerns regarding water resource management and environmental sustainability, understanding land use change and the hydrological health of watersheds is critical for informed decision-making. This study aimed to explore the effect of land use changes on hydrological health resilience in the Rejoso watershed, East Java, using remote sensing techniques and geographic information system tools to characterize the various land cover types. Landsat ETM 7+ satellite imagery was used to describe land cover classes. Hydrological health indicators such as water transmission, water availability during the dry season, and peak rainfall buffer events were systematically analyzed in relation to land cover change conditions. Regression statistical methods were used to measure the impact of land cover changes on hydrological parameters. The study results showed that the area of forest land in the Rejoso watershed tended to increase from 2011 to 2021; on the other hand, the area of agroforestry land tended to decrease along with the increase in upland land. In general, the hydrological health of the Rejoso watershed is decreasing from year to year. The increase in forest area, agroforestry, settlements, and ponds provides a positive response to the hydrological health of the watershed. On the other hand, the increase in moorland and rice fields has a negative impact on the hydrological health of the watershed.